The Potential of Halal Food as A Driver of the Economic Development in Regional Community - Hisam Ahyani; Muntaha Mahfud; Rohmat Waluyo; Widadatul Ulya; Muharir Muharir (Jurnal Pariwisata Terapan, 2020)
This study aims to describe local specialties that have the potential to become halal food in order to boost the economy of local communities in three areas including Lakbok sub-district, Kedungreja sub-district, and Wangon sub-district. In the halal food sector or halal food in Indonesia, especially in the Era of the Industrial Revolution 4.0, as it is now, it has become a necessity. This is because 1) Indonesia is one of the largest Muslim population in the world. 2) traditional regional specialties also need to be developed in order to boost the economy of the local community. 3) Support from the government in an effort to make Indonesia the world's halal center. 4) If the potential of the halal industry is not developed, it will become a threat to the Indonesian economy. This research method uses field studies with data obtained from observations and interviews and documentation. The results showed that halal food in the three sub-districts was able to boost the economy of the people in the area, as evidenced by the sufficient daily needs needed by the people in the three sub-districts. Various foods that can be used as halal food in these three sub-districts are varied, including cassava based chips, Tape, Cimplung or Kulub and Ciu, from soybean ingredients including Sule and Tempe Mendoan, from legen ingredients (coconut juice) can be made into Javanese sugar / brown sugar and can also be used as a mixture for making apem / cake foods. However, from the potential of halal food, some are already labeled halal and some are not labeled halal. This is what makes halal food in these three sub-districts less attractive to consumers. Penelitian ini bertujuan untuk mendeskripsikan makanan khas lokal daerah yang berpotensi menjadi makanan halal (halal food) guna mendongkrak perekonomian masyarakat daerah yang berada di tiga wilayah meliputi kecamatan Lakbok, kecamatan Kedungreja, dan kecamatan Wangon. Dalam sektor makanan halal atau halal food di Indonesia khususnya di Era Revolusi Industri 4.0 seperti sekarang ini telah menjadi sebuah keniscayaan. Hal ini dikarenakan 1) Indonesia masuk pada penduduk muslim terbesar di Dunia. 2) makan tradisional khas daerah juga perlu dikembangkan dalam rangka mendongkrak perekonomian masyarakat setempat. 3) Dukungan dari pemerintah dalam usaha menjadikan Indonesia sebagai pusat halal dunia. 4) Jika potensi industri halal ini tidak dikembangkan maka justru menjadi ancaman bagi perekonomian Indonesia. Metode penelitian ini menggunakan studi lapangan dengan data yang diperoleh dari hasil observasi dan wawancara serta dokumentasi. Hasil penelitian menunjukan bahwa halal food di tiga kecamatan tersebut mampu mendogkrak perekonomian masyarakat di wilayah tersebut, dibuktikan dengan cukupnya kebutuhan sehari-hari yang diperlukan oleh masyarakat di tiga kecamatan tersebut. Aneka makanan yang dapat dijadikan sebagai halal food di tiga kecamatan ini beragam, diantaranya dari berbahan singkong adalah Kripik, Tape, Cimplung atau Kulub dan Ciu, dari bahan kedelai meliputi Sule dan Tempe Mendoan, dari bahan legen (air nira kelapa) dapat dijadikan buat menjadi gula jawa / gula merah dan dapat juga dijadikan sebagai campuran pembuatan makanan apem/kue. Namun dari potensi halal food tersebut ada yang sudah berlabel halal dan juga ada yang belum berlabel halal. Inilah yang menjadikan halal food ditiga kecamatan tersebut kurang diminati oleh konsumennya.